Analysis of internal environment of a pig house using energy recovery ventilator - Byeong Eun Moon; Hee Tae Kim; Kyu Dong Nah; Jin Hyun Kim; Hyeon Tae Kim (Tropical Agricultural Research, 2015)
In this study, Energy Recovery Ventilator (ERV) was applied in a pig house model where the internal temperature, relative humidity, and CO2 were analyzed. The experiment was performed in a pig house model where an ERV was installed and two pigs (8 months, ca. 20 kg) were bred. In the pig house model, the internal temperature, relative humidity, and CO2 were divided into three cases and were then measured. In Case (A), ventilating fan and ERV were not used. In Case (B), a ventilating fan was installed and operated. In Case (C), an ERV was installed and operated in the pig house model. In Case (A), the internal temperature between 12:00-17:00 hours was measured at about 23-24°C, which was lower than usual temperature for breeding. For Case (B), the internal temperature was 22-25°C and the relative humidity was about 70-80%. In Case (C), the internal temperature was 29-32°C.   Tropical Agricultural Research Vol. 26 (3): 547 – 553 (2015)